Evaluating The Relation Between Organizational Learning Culture And Customer Satisfaction Using Job Satisfaction’s Mediating Variable In Insurance Industry - Maleki, Alireza (The Turkish Online Journal of Design Art and Communication, 2016)
The number of carried out activities in the academic field with the subject of organizational learning culture, customer satisfaction and job satisfaction has not been limited in Iran but in the meantime, distinction between different types of organizational learning has been neglected while on the other hand, addressing the issues of customer satisfaction and job satisfaction in the organizations such as insurances are considered as a necessity. Thus, this research tries to review the effect of organizational learning culture on customer satisfaction using job satisfaction’s mediating variable. Therefore, given the importance of this research, first we tried to identify, count and classify learning organizations and organizational learning and then determine the different types of learning and factors in this field and in the next step, customer and customer relationship management and their impact on customer satisfaction and job satisfaction were evaluated. The results of the research showed that there is a separate positive relation between each of organizational learning culture, customer satisfaction and job satisfaction variables.
Keywords: customer satisfaction; organizational learning culture; job satisfaction; the insurance industry